Kekerasan Produk Metalurgi Serbuk Berbahan Limbah Aluminium dengan Metode Kompaksi Bertahap - IGAK Chatur Adhi WA; Anak Agung Alit Triadi; Made Wijana; I Made Nuarsa; I Made Mara (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The product resulting from the powder metallurgy process has advantages in terms of mechanical properties and physical properties. Material engineering by mixing several types of metal powders is very possible to do. The composition of this powder metallurgical process material is a mixture of aluminum powder (80%), copper powder (15%) and silicon carbide powder (5%) by weight then compacted with a compaction load gradually, starting with a load of 3 tons, holding for 3 minutes, followed by a load of 3 tons. 4 tons were held for 3 minutes and the last 5 tons were held for 3 minutes by pre sintering 1250C. Sintering in the  kitchen with temperature variations of 4500C, 5000C and 5500C and sintering time for 60 minutes. Tests carried out on the specimens were hardness tests using the Rockwell (HRF) method. The results showed that the hardness of a single material has a hardness of around 35 HRF. The average hardness of the mixed material at a sintering temperature of 4500C is 80 HRF. The hardness of the mixed material at a sintering temperature of 5000C on average is 74 HRF. Meanwhile, the hardness of the mixed material at a sintering temperature of 5500C averaged 52 HRF. It can be concluded that the application of heat at the time of compaction and the selection of the sintering temperature greatly affect the hardness of the product resulting from the powder metallurgy process.